Pengaruh Harga, Kualitas Produk, dan Brand Trust Terhadap Keputusan Pembelian Pada Produk JPStar - Putu Sinta Dewi, Ni; HS, Rusminah (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of price, product quality, and brand trust on purchasing decisions on JPStar products. The data collection method used a sample survey method with a sample of 100 respondents. The analysis method uses multiple linear regression analysis using the Statistical Package For The Social Sciences (SPSS) tool. The results of the study show that first, Price has a positive and significant effect on Purchasing Decisions with a t value for the Price variable of 3.714> 1.984 Second, Product Quality has a positive and significant effect on Purchasing Decisions with a t value for the Product Quality variable of 2.501> 1.984. Third, Brand Trust has a positive and significant effect on Purchasing Decisions with a t value for the Brand Trust variable with a t value for the Brand Trust variable of 2.658> 1.984. The results of this study can be used as a basis for improving Purchasing Decisions by developing the quality of Price, Product Quality, and Brand Trust.